2008
DOI: 10.1016/j.jbbm.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

HPLC method for determination of verapamil in human plasma after solid-phase extraction

Abstract: A simple, rapid and precise HPLC method has been developed for the assay of verapamil in human plasma. The clean up of the plasma samples was tested using several adsorbents for solid-phase extraction and best recovery was obtained using mixed-mode cartridges (HLB -hydrophilic-lipophilic balance) ranging between 94.70 and 103.71%. HPLC separation was performed with isocratic elution on Lichrospher 60 RP-select B column (250 mm × 4 mm I.D., 5 μm particle size). The mobile phase was 40% acetonitrile and 0.025 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
12
0
3
Order By: Relevance
“…The methods used for verapamil quantification in plasma samples include GC (Hege, 1979), GC/MS (Hynning et al, 1988), HPLC with fluorescence (Sawicki, 2001;Jhee et al, 2005) or ultraviolet detection (Lau-Cam and Piemontese, 1998;Ivanova et al, 2008) and liquid chromatographic-mass spectrometric methods (Von Richter et al, 2000;Hedeland et al, 2004). All of the above methods require a large volume (at least 500 mL) of plasma sample.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used for verapamil quantification in plasma samples include GC (Hege, 1979), GC/MS (Hynning et al, 1988), HPLC with fluorescence (Sawicki, 2001;Jhee et al, 2005) or ultraviolet detection (Lau-Cam and Piemontese, 1998;Ivanova et al, 2008) and liquid chromatographic-mass spectrometric methods (Von Richter et al, 2000;Hedeland et al, 2004). All of the above methods require a large volume (at least 500 mL) of plasma sample.…”
Section: Introductionmentioning
confidence: 99%
“…The eluents were monitored at 278 nm (AUFS = 1). The injection volume was 20 µL and eluted at a flow rate of 1.0 mL min −1 at 30 °C …”
Section: Methodsmentioning
confidence: 99%
“…12 In patients with hepatic insufficiency, metabolism is delayed and elimination half-life is prolonged up to 14-16 hours. These include spectrophotometry, 15 high performance liquid chromatography (HPLC) with spectrophotometric detection, [16][17][18][19][20][21] high performance thin layer chromatography, 22,23 and liquid chromatography-tandem mass spectrometry (LC-MS/MS). † These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…12 Many methods have been reported for the analysis of this combination or one of its components in pharmaceuticals or body fluids. These include spectrophotometry, 15 high performance liquid chromatography (HPLC) with spectrophotometric detection, [16][17][18][19][20][21] high performance thin layer chromatography, 22,23 and liquid chromatography-tandem mass spectrometry (LC-MS/MS). 24,25 Several pharmacokinetic studies have been reported for these drugs.…”
Section: Introductionmentioning
confidence: 99%